INTERFERENSI BAHASA BETAWI DALAM CERPEN MAHASISWA JURUSAN PBSI FITK UIN SYARIF HIDAYATULLAH JAKARTA - Siti Sahara (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
This study tried to see how far the interference of Betawi language in Department of Education Indonesian Language and Literature students’ short story, Faculty of Tarbiya and Teaching Sciences, Syarif Hidayatullah State Islamic University of Jakarta? It would be interesting to make a research about it, because the location of the campus, located on the border between Jakarta and Tangerang, Banten. Therefore the researcher assumed it would be found the Betawi language interference in students’ short story.The method of this research is combining quantitative and qualitative. Quantitative used to see the amount of Betawi language interference while qualitative used to describe forms of interference that are found. The sample data of this study is the short story created by students from the Department of Education Indonesian Language and Literature which organized to fulfill the assigment of writing subject.The results obtained in this study as follow: 1) the forms of interference were found: the interference of word, affixation interference which include prefix, suffix, confix, and the repetition of the word; 2) The amount for each interference that occurs; (a) Interference of suffix is most present in 23 (36.51%); (b) Interference in the category of prefix were 12 (19:05%), (c) interference in confix category were 9 or 14:28%, and (d) Interference in the form of word categories were 19 (30.15%). There were 63 morphological interference from 36 students’ short stories.